'When God sees us in the circuses': Salvian of Marseille's De gubernatione Dei and the critique of Roman society. Issue 1 (21st December 2022) - Stutz, Jonathan
Abstract : This article addresses Salvian of Marseille's treatise on God's governance ( De gubernatione Dei ), one of the most important sources for the Germanic peoples' period of migration at the beginning of the fifth century. It focuses in particular on Salvian's critique of public entertainment, in the middle of Book VI. As I would like to show, his invective against this aspect of Roman life is closely connected to the theme underlying the entire treatise, since it offers a key argument for Salvian's attempt to demonstrate collective responsibility for the present crisis. At the same time, the author's critique of the circus and the theatre stands as a defining point in his greater appeal for moral reform, letting him challenge the desire in Trier to bring back the city's glorious past through a restoration of public entertainment.